To improve the academy : (Anker Publishing company, Inc, 2003)
To Improve the Academy, Volume 21, reflects upon the current and emerging trends in practicing faculty development in higher education. The book is divided into four sections: Faculty Development and Its Role in Institutional and National Crisis: reflects upon the events of September 11 and looks toward the changing face of American higher education. Faculty Focus in Faculty Development: contains chapters that focus on the needs of faculty with respect to enhanced development. Student-Centered Faculty Development: discusses the role that students play in the teaching and learning process. Philosophical Issues in Faculty Development: considers the potential effect of new technologies on the future of higher education